2017
DOI: 10.18275/fire201704011083
|View full text |Cite
|
Sign up to set email alerts
|

Empowered but not Equal: Challenging the Traditional Gender Roles as Seen by University Students in Saudi Arabia

Abstract: This study examines perspectives of Saudi university students regarding changing gender roles as affected by women's rights, education, employment, and activity in the public sphere. Results from a questionnaire distributed among 4,455 male and female students indicate students are confident and optimistic about improving gender equity, however resistance from those holding traditional views still exist. Female respondents are more optimistic than male respondents,seeing changes in gender roles as advantageous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…Moreover, the item of " I have the opportunity to participate in social activities " was ranked fourth with a mean of ( 2.44), the item of " my present life is better than my past life " was ranked fifth with a mean of ( 2.39), and "I get the social support I need" was ranked sixth with a mean of (2.38). This result is consistent with Al- Bakr et al (2017) that the present generation accepts the change of gender roles and admits woman's rights in education, employment and public activity. Al-Zahrani (2020) showed a correlation between quality of life, social support, and self-efficacy.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the item of " I have the opportunity to participate in social activities " was ranked fourth with a mean of ( 2.44), the item of " my present life is better than my past life " was ranked fifth with a mean of ( 2.39), and "I get the social support I need" was ranked sixth with a mean of (2.38). This result is consistent with Al- Bakr et al (2017) that the present generation accepts the change of gender roles and admits woman's rights in education, employment and public activity. Al-Zahrani (2020) showed a correlation between quality of life, social support, and self-efficacy.…”
Section: Resultssupporting
confidence: 87%
“…This result is consistent with Al- Bakr et al (2017) that the current generation accepts changing gender roles and accepts women's rights in education, employment and public activity. The item of "the present lifestyle negatively affects social relationships" was ranked seventh with a mean of (2.13).…”
Section: Resultssupporting
confidence: 87%
“…This accomplishment can be included as a core expectation from users given that online learning through smart devices reduces the effort and time required to complete learning tasks and reflects academic performance as accurately as possible [36], [41]. Effort is a concern of the target users, and the statistical results indicated that expected effort is significantly associated with both genders.…”
Section: A Effects Of Gendermentioning
confidence: 98%
“…Saudi women are entering the workforces, participating as leaders in university education. These phenomena are examples of women transitioning to decision making roles (Al-bakr, Bruce, Davidson, Schlaffer, & Kropiunigg, 2017). Such engagement of women in the economic exercise is proven has positive impacts on the national economy as well as household wellbeing of Saudi (Nisreen & Nadia, 2011).…”
Section: Introductionmentioning
confidence: 99%